Relationships between body composition and anaerobic performance parameters in female handball players - Mehmet Kale; Erkan Akdoğan (Physical Education of Students)
Background and Study Aim. The purpose of this study was to investigate of the relationships between total/segmental body composition and anaerobic performance parameters in female handball players.